Soybean β-conglycinin and glycinin reduced growth performance and the intestinal immune defense and altered microbiome in juvenile pearl gentian groupers Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂ - Yuanfa He (Animal Nutrition, 2022)
The utilization efficiency of soy protein is affected by its 2 anti-nutritional substances—the antigens β-conglycinin and glycinin. This study investigated their effects on the growth performance, intestinal immune defense, and microbiome in juvenile pearl gentian groupers (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂). Three isonitrogenous and isolipidic diets were formulated containing fishmeal supplemented with 70 g/kg β-conglycinin or 100 g/kg glycinin, or no supplementation (control). Each experimental diet was fed to quadruplicate groups with 30 fish in each tank for 8 weeks. Dietary inclusion of either β-conglycinin or glycinin significantly reduced weight gain and specific growth rates, and cell proliferation of the distal intestine. Histological evaluation of the intestine tract revealed the inflammation signs, characterized by reducing of plica height and width as well as the number of the goblet cells, and widening of the lamina propria. The group fed the β-conglycinin diet had reduced lysozyme activity, contents of immunoglobulin M and complements 3 and 4. Increased activities of caspase-3 and -9 were observed in the group fed the β-conglycinin diet compared to the other 2 groups. In the intestinal microbiota, the relative abundances of the potentially pathogenic genera Photobacterium and Vibrio were significantly higher in the glycinin group than those in others. Therefore, the existence of soybean antigens (β-conglycinin or glycinin) could damage the structural integrity of the intestine, reduce immune defense, reshape the intestinal microbiome and, ultimately, impair growth in fish.